A Study of Community College Faculty Work Expectations: Generous Educators and Their Managed Generosity. Issue 3 (4th March 2021) - Aguilar-Smith, Stephanie; Gonzales, Leslie D.
ABSTRACT: In this multi-method qualitative study, which included faculty and administrator interviews as well as a systematic analysis of organizational documents, we sought to understand the expectations placed upon and taken up by community college faculty. Our analysis suggests that the overarching expectation of community college faculty is to serve as generous educators . However, despite seeming consensus across data sources, we found that faculty and administrators often held discrepant views as to how faculty should carry out this role. Whereas most community college faculty relationally and holistically conceived of their work, administrators generally favored instrumental and bureaucratic techniques, leading us to argue that the generosity of these educators is highly managed. Similar to earlier writing on managed professionals, we found that administrators expected faculty to entrust their efforts to care for students to bureaucratic devices, although faculty often considered such systems ineffective. Ultimately, we assert that the instrumental framing of community college faculty work expectations adversely affects not just faculty but students, and we offer recommendations for community college leaders and faculty development offices.